Penerapan Algoritma One Time PAD pada e-Mail Client berbasis Web - Fatmasari (LPPM STMIK Antar Bangsa, 2025)
Electronic mail (e-mail) is currently one of the internet features that are now commonly used and play a role in sending letters electronically. Fast delivery does make it easier for users, but this also increases the leak of messages that are usually sent without security (plain text). So for some important messages, it can be done by applying cryptography when sending and reading e-mail. And from the many cryptographic algorithms that exist, One Time Pad is one that can be used in this condition and this algorithm will be discussed in this paper.